Vespidae (Insecta: Hymenoptera) of Multan Region, Pakistan. (2nd October 2022) - Qasim, Muhammad; Carpenter, James M.; Bokhari, Syed Habib Ali; Khan, Muhammad Rafique; Rafi, Muhammad Ather; Amin, Muhammad; Siddiqui, Junaid Ali; Hassan, Muhammad Asghar
ABSTRACT: A total 14 species from 10 genera belonging to three subfamilies: Eumeninae, Polistinae and Vespinae are listed from the Multan region of Pakistan. The subfamily Eumeninae is represented by 11 species in eight genera, while there are two species of genus Polistes belonging to the subfamily Polistinae and one species of the genus Vespa belonging to subfamily Vespinae. Among these Allorhynchium argentatum, Antepipona ceylonica, Delta esuriens esuriens, Delta pyriforme pyriforme, Odynerus reniformis, Xenorhynchium nitidulum, Polistes indicus, Polistes wattii and Vespa orientalis are recorded for the first time from Multan region. Genus Odynerus and two species: Antepipona ceylonica, and Odynerus reniformis are new records from Pakistan.